Design of cross border healthcare integrated system and its privacy and security issues - Savoska, Snezana; Jolevski, Ilija; Ristevski, Blagoj; Blazheska-Tabakovska, Natasha; Bocevska, Andrijana; Jakimovski, Boro; CHorbev, Ivan; Kilintzis, Vassilis (My University, 2019)
Healthcare systems generate large amounts of data, collected from different healthcare systems and sources and stored in large data sets. It is particularly interesting for a wide range of user groups and stakeholders in healthcare. As the data volume increases over time, the risk of abuse and unauthorized access to the personal and sensitive data arises. Data are collected by using of numerous means and are stored in different datacenters. These data are related to the patients, doctors, insurance companies, health providers and other users as stakeholders in one or more countries, and data can be a subject of misuse at many levels. When dealing with such complex systems, a complex data security management is needed. IPA 2 project Cross4all intends to integrates health and social care system across the border area and gather patient data from both sides of the Republic of N. Macedonia and Greece. We proposed a model of secure system architecture that deals with the data security and privacy standards of two countries taking into account their data protection regulations and laws.
Keywords: healthcare data security and privacy, healthcare integrated system, healthcare services, mobile applications